Primary intracranial spindle cell sarcoma with rhabdomyosarcoma-like features share a highly distinct methylation profile and DICER1 mutations - Koelsche, C (2022)
Patients with DICER1 predisposition syndrome have an increased risk to develop pleuropulmonary blastoma, cystic nephroma, embryonal rhabdomyosarcoma, and several other rare tumor entities. In this study, we identified 22 primary intracranial sarcomas, including 18 in pediatric patients, with a distinct methylation signature detected by array-based DNA-methylation profiling. In addition, two uterine rhabdomyosarcomas sharing identical features were identified. Gene panel sequencing of the 22 intracranial sarcomas revealed the almost unifying feature of DICER1 hotspot mutations (21/22; 95%) and a high frequency of co-occurring TP53 mutations (12/22; 55%). In addition, 17/22 (77%) sarcomas exhibited alterations in the mitogen-activated protein kinase pathway, most frequently affecting the mutational hotspots of KRAS (8/22; 36%) and mutations or deletions of NF1 (7/22; 32%), followed by mutations of FGFR4 (2/22; 9%), NRAS (2/22; 9%), and amplification of EGFR (1/22; 5%). A germline DICER1 mutation was detected in two of five cases with constitutional DNA available. Notably, none of the patients showed evidence of a cancer-related syndrome at the time of diagnosis. In contrast to the genetic findings, the morphological features of these tumors were less distinctive, although rhabdomyoblasts or rhabdomyoblast-like cells could retrospectively be detected in all cases. The identified combination of genetic events indicates a relationship between the intracranial tumors analyzed and DICER1 predisposition syndrome-associated sarcomas such as embryonal rhabdomyosarcoma or the recently described group of anaplastic sarcomas of the kidney. However, the intracranial tumors in our series were initially interpreted to represent various tumor types, but rhabdomyosarcoma was not among the typical differential diagnoses considered. Given the rarity of intracranial sarcomas, this molecularly clearly defined group comprises a considerable fraction thereof. We therefore propose the designation "spindle cell sarcoma with rhabdomyosarcoma-like features, DICER1 mutant" for this intriguing group.